2019
DOI: 10.3390/educsci9020153
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Hearing Technology for Deaf and Hard-of-Hearing Spoken Language Learners

Abstract: Radical advancements in hearing technology in the last 30 years have offered some deaf and hard-of-hearing (DHH) children the adequate auditory access necessary to acquire spoken language with high-quality early intervention. However, meaningful achievement gaps in reading and spoken language persist despite the engineering marvel of modern hearing aids and cochlear implants. Moreover, there is enormous unexplained variability in spoken language and literacy outcomes. Aspects of signal processing in both heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 129 publications
0
7
0
Order By: Relevance
“…Early language exposure has been related to proficiency in language and academic achievement, whether it is signed [23,24] or spoken [25]. Earlier studies showed that deaf students with deaf parents demonstrated greater language abilities and academic performance and that their language milestones were developmentally similar to hearing children [16,24,26], indicating that deaf children were capable of developing language at normal rates with accessible input [20].…”
Section: Deaf Education and Language Developmentmentioning
confidence: 99%
“…Early language exposure has been related to proficiency in language and academic achievement, whether it is signed [23,24] or spoken [25]. Earlier studies showed that deaf students with deaf parents demonstrated greater language abilities and academic performance and that their language milestones were developmentally similar to hearing children [16,24,26], indicating that deaf children were capable of developing language at normal rates with accessible input [20].…”
Section: Deaf Education and Language Developmentmentioning
confidence: 99%
“…It has been argued that d/Dhh students follow a developmental learning trajectory that is similar to that of typical literacy learners-albeit some students will proceed at a slower quantitative rate due to a number of variables such as the quality of interventions, effectiveness of early amplification, variability in teacher competency, and so on [7,9,11,19,22]. This phenomenon, coined the Qualitative Similarity Hypothesis (QSH) asserts that, regardless of the degree of hearing acuity, d/Dhh students need to acquire proficiency in the same group of fundamentals associated with code-related, language-related (e.g., English language proficiency), and comprehension-related skills that are necessary for the development of typical literacy skills [8,10,33].…”
Section: The Qualitative Similarity Hypothesismentioning
confidence: 99%
“…Traditionally, other elements of this complexity have often included d/Dhh students with disabilities (or additional disabilities) and those-for whatever reason-who come to school with limited proficiency in any language [17,18]. It is also critical to consider the advancement of sophisticated listening technologies and their contributions to the development of language and literacy; this advancement has spawned an evolving demography of d/Dhh children and adolescents [14,19,20]. Other important areas covered in this Special Issue include the assessment of language and literacy [21] and the influence of inclusion on the development of language and literacy skills [22].The plan for this concluding article is as follows: First, we discuss the need for researchers to document adequate demographics and other critical background characteristics of the samples in their investigations.…”
mentioning
confidence: 99%
“…Supplementary aids mentioned in the supervisor's answer include, but are not limited to, physical, environmental, behavioral, social, and instructional modification and adaptation services (Holt, 2019). Supplementary aids help enable DHH students to be educated along with their peers to the maximum extent appropriate (Burns, 2003).…”
Section: Support Servicesmentioning
confidence: 99%
“…The education policy focuses on the human development model to evaluate DHH students and does not employ other models. Understanding how inclusive education occurred through various models and supported services (Burns, 2003) promotes positive outcomes (Holt, 2019; Kyzar et al, 2016). Previous research in this area is insufficient to explain the role of institutional practice in promoting inclusive education in schools (Almalki, 2022; Alsalman et al, 2018; Baothman & AlSudairi, 2018).…”
Section: Introductionmentioning
confidence: 99%